2013
DOI: 10.1002/app.40074
|View full text |Cite
|
Sign up to set email alerts
|

Architectural characteristics of stochastic honeycombs fabricated from varying melt strength polypropylenes

Abstract: Stochastic honeycombs are a cellular polymer fabricated through a simple melt-stretching process. In this study, five polypropylenes (PP) with varying rheological properties were used to fabricate stochastic honeycombs over a range of densities. Rheology tests were performed to determine the melt behavior, while micro-CT scans were used as a nondestructive characterization technique to determine the internal architecture. The sandwich structure consists of parallel skins separated by a network of interconnecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…In Stage IV, the stress reaches a nearly constant value as the final web pattern has been formed and the webs stretch at the plateau extensional value (σ ext ). Some of the webs undergo ductile failure as the sample is stretched to its final height, t final , and partial webs and archways are formed . Note that previous work showed that there was some small increase in the crystallinity of the PP in the webs compared to the PP with no thermal history, implying that some strain‐induced crystallinity occurs as a result of melt stretching .…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…In Stage IV, the stress reaches a nearly constant value as the final web pattern has been formed and the webs stretch at the plateau extensional value (σ ext ). Some of the webs undergo ductile failure as the sample is stretched to its final height, t final , and partial webs and archways are formed . Note that previous work showed that there was some small increase in the crystallinity of the PP in the webs compared to the PP with no thermal history, implying that some strain‐induced crystallinity occurs as a result of melt stretching .…”
Section: Resultsmentioning
confidence: 96%
“…While the process to fabricate stochastic honeycombs is simple, their internal architecture is not. Previous work analyzed the three‐dimensional architecture of stochastic honeycombs through X‐ray tomography using area fractions and Minkowski functionals (surface area, volume, and Euler number) . The cross‐sectional area fraction (area of the skin or webs/area of the sample) was shown to decrease from 1 at the upper and lower skins to a plateau over the central third of the sample height, which varied with the relative density of the sample .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations